A. A. TARAN: SECONDARY CONTEXT NOMINATIONS IN THE MODERN UKRAINIAN LANGUAGE - TARAN, A. A. (Linguistic Bulletin (Movoznavchyi Visnyk), 2021)
Summary. Introduction. It has been found that the secondary nomination is based on the associative nature of human thinking. The words reflect the processes of living contemplation of the human environment, there is a semantic rethinking of known names and their gradual codification. The formation and creation of a new concept or a new perception of the subject is carried out on the basis of existing language material. Purpose – to analyze non-autonomous (interword, context-dependent) secondary nominations in the modern Ukrainian language. Results. The formation of a new meaning of a lexical unit can occur within the word and lead to the so-called autonomous secondary nomination or within the phrase. Such contextually dependent new meaning of the word is qualified as a consequence of non-autonomous secondary nomination. The precondition for the emergence of new meanings of words is a new context of their use, which in turn reveals their new lexical and syntactic compatibility and the very type of new meaning, the way it is formed. For subject names, it is primarily their new definitions, for symbolic names – their new objects of definition. The formation of new values of adjectives is facilitated by changing the function in compounds with subject names, for example, the function of identification, or the function of indicating the relationship of one object to another, the characteristic function, or the function of distinguishing such an object from others, emphasizing its other quality. The new context of use signals the emergence of new values. Originality. The semantics of the word implies its compatibility. Regardless of use, any word is in the mind of the bearer in all meanings, potential and hidden, which are realized in context in need. However, the differentiation of meanings itself depends on compatibility with other words, which is a confirmation that any meaning of a word is realized in context. Therefore, the study of word compatibility is extremely important for understanding the meaning of words, because context analysis always implements the individual semantic features of each word. Conclusion. New explanatory dictionaries of the Ukrainian language should testify to the development of semantic potential of words, and for this purpose it is necessary not only to describe secondary nominations of different types, but also to develop a conceptual apparatus for their analysis, criteria for their standardization and codification.